Plasminogen Activating Inhibitor-1 Might Predict the Efficacy of Anti-PD1 Antibody in Advanced Melanoma Patients - Ohuchi, Kentaro; Kambayashi, Yumi; Hidaka, Takanori; Fujimura, Taku (Frontiers in Oncology, 2021)
Plasminogen activating inhibitor-1 (PAI-1) plays crucial roles in the development of various cancers, including melanomas. Indeed, various pro-tumorigenic functions of PAI-1 in cancer progression and metastasis have been widely reported. Among them, PAI-1 is also reported as a key regulator of PD-L1 expression on melanoma cells through endocytosis, leading to abrogating the efficacy of anti-PD1 antibodies (Abs). These findings suggested that PAI-1 expression might predict the efficacy of anti-PD1 Abs. In this report, the expression and production of PAI-1 in melanoma patients were evaluated, and the immunomodulatory effects of PAI-1 on tumor-associated macrophages were investigated in vitro. Immunohistochemical staining of PAI-1 showed that PAI-1 expression on melanoma cells was significantly decreased in responders compared to non-responders. Moreover, baseline serum levels of PAI-1 were significantly decreased in responders compared to non-responders. Notably, PAI-1 decreased the production of various chemokines from monocyte-derived M2 macrophages in vitro, suggesting that PAI-1 might decrease tumor-infiltrating lymphocytes to hamper the anti-tumor effects of anti-PD1 Abs. These results suggest that baseline serum levels of PAI-1 may be useful as a biomarker for identifying patients with advanced cutaneous melanoma most likely to benefit from anti-melanoma immunotherapy.